Reinterpreting identity: The influence of bureaucracy, situation definition, discrimination, and elites in Islamic education - Badruzaman, Abad; Adiyono, Adiyono (Journal of Research in Instructional, 2023)
The aim of this research is to understand in depth the phenomenon of identity reinterpretation, exploring how bureaucracy influences the definition of the situation of students and teachers, the role and effects of elite groups in determining the direction of Islamic education, and how this influences social interactions in Islamic societies. The research also discusses the changes and improvements needed to create a more inclusive and equitable Islamic education. This study uses a qualitative method. This method was chosen because this research aims to understand the phenomenon of identity reinterpretation in Islamic education in depth. This research uses in-depth interview techniques to collect data. Interviews were conducted with various informants: teachers, students, and Islamic education officials. This research explores how bureaucracy in the Islamic education system influences the definition of the situation of students and teachers, especially in the context of the emergence of discrimination or inequality. In addition, this research can examine the role and impact of elite groups in determining the direction of Islamic education and how this influences social interactions in Islamic societies. This research will discuss changes and improvements that may be needed to create more inclusive and equitable Islamic education.